Особливості державного управління та регулювання розвитку вітроенергетики України - Розуменко, Світлана Миколаївна; Розуменко, Светлана Николаевна; Rozumenko, Svitlana (Мелітополь: Люкс, 2015)
UK: Одним із найбільш важливих напрямів енергетичної політики України є використання відновлюваних джерел енергії. В статті досліджено особливості державного регулювання розвитку вітроенергетики України, розглянуто потенціал відновлювальних джерел енергії, напрямки державної політики щодо розвитку вітроенергетики в Україні. EN: Raising of problem. The use of renewable energy is one of the most important directions of Ukraine's energy policy aimed at saving traditional energy resources and improve the surrounding environment. Increased use of renewable energy sources in the energy balance of Ukraine will help improve the diversification of energy sources that contribute to the energy independence of the country. Basic material of research. Ukraine has significant potential renewable energy that can be used to improve the trade balance, create jobs and stimulate economic activity at a time when the country has overcome the critical economic challenges such as increasing dependence on energy imports and the need to urgently upgrade outdated basic production assets in the energy sector. The International Renewable Energy Agency (IRENA) on the results of analytical studies and taking into account the various barriers that slow down the development of renewable energy in Ukraine, have developed proposals whose implementation will accelerate the deployment of renewable energy in Ukraine: Modernization and efficiency of existing electricity and heating capacities from making investments in energy efficiency and renewable energy; Increase domestic and foreign investment in new capacity by simplifying procedures for obtaining qualifications green tariff adoption of incentives for small investors and creating financing in the form of bank debt available products such as guarantees on loans; Increasing awareness of the resource potential costs and benefits of renewable energy sources and develop rules, regulations, standards and definitions. Use of local production capacity for the creation of affordable equipment market for renewable energy; Development of a national plan of transmission and distribution lines, comprising more than 15% share of electricity generation from. Conclusions. To further improve the mechanism of state regulation of wind energy Ukraine should: improve legislation in the field of renewable energy and energy in general with the approach it with European norms and standards; develop sectoral program for the development of wind energy in Ukraine; a state program of development of the industry, to develop a national plan for the development of wind power with the assistance of the European partners of Ukraine, the producers of wind electricity; provide high-tech research, training and skills development for industry development.
Keywords: енергетична політика; відновлювальні джерела енергії; вітроенергетика; державне регулювання